Integrating Augmented Reality and Simulation Game for Flower Board Design - Pratiwi, Eka; Triase, Triase; Sinaga, Imam Adlin (Information Technology and Science (ITScience), 2024)
Augmented Reality was regarded as one of the technologies that merged the real world with the virtual one. Its development was carried out by developers across various fields, including businesses such as floral services, exemplified by Berkah Florist. In practical application, Berkah Florist encountered challenges related to efficiency and customer satisfaction in the floral design process. The prevailing methods, such as displaying photographs or employing paper-based designs, were time-consuming and susceptible to paper damage, thus hindering customers from expressing their preferences accurately and disrupting the design process. To address these challenges, an application was developed to streamline the floral design process, aiming to make it more appealing. This research aimed to assist customers and streamline Berkah Florist's operations by facilitating the modeling and visualization of more captivating and effective designs. The application, based on a simulation game, was developed using Research and Development (R&D) and Rapid Application Development (RAD) methodologies. The application presented floral designs through an AR-enabled camera, replicating real-world conditions. The incorporation of Augmented Reality in the application garnered interest and engagement from prospective customers while alleviating boredom. Designed to provide a delightful experience for potential customers, the application aimed to enhance their interest in reusing it. Consequently, Berkah Florist could enhance customer experience and improve efficiency in the floral design process.